Incomplete Assembly of the Dystrophin-Associated Protein Complex in 2D and 3D-Cultured Human Induced Pluripotent Stem Cell-Derived Cardiomyocytes - Gilbert, Guillaume; Kadur Nagaraju, Chandan; Duelen, Robin; Amoni, Matthew; Bobin, Pierre; Eschenhagen, Thomas; Roderick, H. Llewelyn; Sampaolesi, Maurilio; Sipido, Karin R. (Frontiers in Cell and Developmental Biology, 2021)
Human induced pluripotent stem cells derived cardiomyocytes (hiPSC-CM) are increasingly used to study genetic diseases on a human background. However, the lack of a fully mature adult cardiomyocyte phenotype of hiPSC-CM may be limiting the scope of these studies. Muscular dystrophies and concomitant cardiomyopathies result from mutations in genes encoding proteins of the dystrophin-associated protein complex (DAPC), which is a multi-protein membrane-spanning complex. We examined the expression of DAPC components in hiPSC-CM, which underwent maturation in 2D and 3D culture protocols. The results were compared with human adult cardiac tissue and isolated cardiomyocytes. We found that similarly to adult cardiomyocytes, hiPSC-CM express dystrophin, in line with previous studies on Duchenne’s disease. β-dystroglycan was also expressed, but, contrary to findings in adult cardiomyocytes, none of the sarcoglycans nor α-dystroglycan were, despite the presence of their mRNA. In conclusion, despite the robust expression of dystrophin, the absence of several other DAPC protein components cautions for reliance on commonly used protocols for hiPSC-CM maturation for functional assessment of the complete dystrophin-associated protein complex.